2003
DOI: 10.1111/j.1538-4632.2003.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Accessibility Revisited: Implications for Geographical Analysis in the Twenty‐first Century

Abstract: Analytical methods for evaluating accessibility have been based on a spatial logic through which the impedance of distance shapes mobility and urban form through processes of locational and travel decision making. These methods are not suitable for understanding individual experiences because of recent changes in the processes underlying contempora y urbanism and the increasing importance of information and communications technologies (ICTs) in people's daily lives. In this paper we argue that analysis of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(142 citation statements)
references
References 70 publications
2
135
0
5
Order By: Relevance
“…While accessibility has traditionally been conceived as proximity of (or cost of travel between) one location and others, cognitive mapping research shows that physical distances are only one factor shaping how individuals make choices in a spatial context (37). Individual differences, including prior modal travel experiences, cultural preferences, and spatial abilities, shape the cognitive map and, thereby, the cognitive proximity and accessibility of potential destinations in a region.…”
Section: Resultsmentioning
confidence: 99%
“…While accessibility has traditionally been conceived as proximity of (or cost of travel between) one location and others, cognitive mapping research shows that physical distances are only one factor shaping how individuals make choices in a spatial context (37). Individual differences, including prior modal travel experiences, cultural preferences, and spatial abilities, shape the cognitive map and, thereby, the cognitive proximity and accessibility of potential destinations in a region.…”
Section: Resultsmentioning
confidence: 99%
“…This situation has started to change since the 1990s, when GISs have become available (Miller 1991;Kwan and Weber 2003) so detailed reconstruction of the movements of a large number of people has become possible (Kwan 1998;Kwan and Weber 2003). The empirical investigations enabled by GISs have shown that detailed microscopic description may yield different results from gravitational or other aggregate models.…”
Section: Figurementioning
confidence: 99%
“…The empirical investigations enabled by GISs have shown that detailed microscopic description may yield different results from gravitational or other aggregate models. In particular, gender differences in the usage of time, behavior induced by time windows such as working times and rush hours, as well as zooming the scale of description cannot be rendered by aggregate models (Kwan and Weber 2003).…”
Section: Figurementioning
confidence: 99%
“…Research of inner-city mobility (Antipova, et al, 2011;Keeling, 2008), accessibility analysis and studies of optimal time-space distributions (Kwan & Weber, 2003;Neutens, et al, 2012;Neutens, et al, 2010;Versichele, et al, 2012) all reveal elements of the spatial distribution and interactions of people and businesses within the two-dimensional urban city.…”
Section: Introductionmentioning
confidence: 99%